Generation and evaluation of a novel PI3K-targeting gene therapy in the failing mouse heart and healthy sheep heart - Sebastian Bass-Stringer; Daniel G. Donner; Clive N. May; Aya Matsumoto; Emma I. Masterman; Aascha A. D'Elia; Yi Ching Chen; Helen Kiriazis; Jieting Luo; Roger Chooi; Clara Liu Chung Ming; Paul Gregorevic; et al. (Journal of Molecular and Cellular Cardiology Plus)
Heart failure (HF) remains a clinical challenge with cardiac dysfunction typically progressing even with treatment, and heart transplants only available to small numbers. We previously identified phosphoinositide 3-kinase (PI3K, p110α) as a master regulator of exercise-induced cardioprotection, and showed that gene therapy, incorporating a constitutively active form of PI3K (caPI3K) improved function of the failing mouse heart. However, this approach was not cardiac-specific and the gene therapy was challenging to manufacture. The aim of this study was to develop new PI3K-based gene therapies with more optimal properties for clinical translation. We generated and assessed adeno-associated viruses (AAV6) encoding various PI3K constructs, with different enhancers, promoters and transgene components in healthy adult male mice. The most promising AAV construct based on AAV expression, cardiac-specificity, and ease of manufacture contained a cardiac troponin T (cTnT) promoter together with a small region of the regulatory subunit of PI3K (iSH2), and an intron from the β-globin gene which enhances transcription (IVS2). This AAV (1 × 1012, 2 × 1012 vg) was administered to mice with myocardial ischemia/reperfusion injury (I/R: 1 h ischemia with reperfusion; AAV delivered 24 h post-I/R). Direct cardiac injections of PI3K-based AAVs were also performed in healthy adult female sheep. I/R mouse hearts treated with the AAV6-cTnT-IVS2-iSH2 displayed increased phosphorylation of Akt, but no improvement in cardiac function or structure was observed. AAV6-cTnT-IVS2-iSH2 successfully transduced healthy sheep hearts which increased endogenous PI3K catalytic activity. Further testing/optimization of the AAV (time of delivery and/or duration) will be required to assess the therapeutic potential of this approach.